Maternal mental health and its association with infant growth at 6 months in ethnic groups: results from the Born-in-Bradford birth cohort study. - Gemma D Traviss; Robert M West; Allan O House (PLoS ONE)
Objective To identify factors associated with infant growth up to 6 months, with a particular focus on maternal distress, and to explore the effect of ethnicity on any relation between maternal distress and infant growth. Methods Cohort study recruiting White and Pakistani women in the United Kingdom (UK). Infant growth was measured at birth and 6 months. Standard assessment of mental health (GHQ-28) was undertaken in pregnancy (26-28 weeks gestation) and 6 months postpartum. Modelling included social deprivation, ethnicity, and other known influences on infant growth such as maternal smoking and alcohol consumption. Results Maternal distress improved markedly from pregnancy to 6 months postpartum. At both times Pakistani women had more somatic and depression symptoms than White women. Depression in pregnancy (GHQ subscale D) was associated with lower infant growth at 6 months. Self-reported social dysfunction in pregnancy (GHQ subscale C) was associated with lower gestational age.. Pakistani women reported higher GHQ scores during pregnancy associated with smaller infants at birth. They lived in areas of higher social deprivation, reported less alcohol consumption and smoking postnatally, all independent influences on growth at 6 months. Conclusions Maternal mental health in pregnancy is an independent influence on infant growth up to 6 months and is associated with ethnicity which was itself associated with deprivation in our sample. There is a complex relationship between symptoms of maternal distress, ethnicity, deprivation, health behaviours, and early infant growth. Measures should include both emotional and somatic symptoms and interventions to reduce risks of poor early growth need to include psychological and social components.